PENGARUH TIME DEMAND OF WORK,WORK LIFE BALANCE DAN TURNOVER INTENTION TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT PINNACEL APPAREL UNIT 3 - Aisyah, Anis Nur; Kurniati, Edi Dwi; Supraptini, Nunuk (BISECER (Business Economic Entrepreneurship), 2024)
Productivity and human resources have an important role for the progress of the company. Because all production activities of the enterprise are strongly influenced by labor in product production (output). The many demands and pressures given by the company to employees where there is continuous work coercion which results in employees feeling their lives are only for work and their personal lives are sidelined so as to make employees stressed or depressed which can hinder work which can hinder the achievement of productivity. So this study aims to determine the effect of Time demand of work, work life balance, Turnover intention on employee work productivity special study of the sewing section at PT. Pinnacel Apparel Unit 3. This study uses a sampling technique in this study conducted by simple random sampling technique probability sampling. Methods of data collection using a questionnaire. The sample in this research is 112 respondents. The analysis technique used is validity test, reliability test, simple and multiple correlation test, simple and multiple regression test, coefficient of determination test and hypothesis test (t test and F test) through SPSS software. The results of the analysis show that the time demand of work variable has an effect on work productivity, with the results obtained that the t count (4.422) > t table (1.982) and a significant level of 0.000 t table (1.982) and a significant value of 0.000 < (1.982) and a significant value of 0.485 > 0.05. This shows that there is no significant effect of turnover intention on work productivity. The results of the study simultaneously obtained a calculated F value (66.952) > F table (3.08) and a significant value of 0.000 <0.05 meaning that the time demand of work, work life balance, and turnover intention variables simultaneously have a positive and significant effect on productivity Work.